Emerging topics and findings the science on teams and teamwork - DiazGranados, Deborah (2008)
Teams are a critical part of organizations today. In this paper we provide a review of the critical topics found in the team literature. This paper reviews the necessary teamwork components and coordinating mechanisms that promote effectiveness. Included is a discussion of the team training strategies that have been developed in order to target success in teams. The paper concludes with several avenues that can be taken by team researchers to address the questions that remain unanswered.